Directors in new technology-based ventures: An empirical inquiry - Garg, Sam; Howard, Michael; Pahnke, Emily Cox (Journal of Business Venturing, 2025)
In the emerging literature on venture boards, little research examines the association between different categories of venture directors and strategic firm outcomes. We conduct an empirical inquiry into how founder-directors, venture capitalist investor-directors and corporate venture investor-directors are related to inter-organizational alliances, innovation, and exits. In our longitudinal study based on hand-collected data on 156 medical device ventures in the US, we find that founder-directors are positively associated with patents and negatively associated with supply chain agreements. VC-directors are positively associated with exits but are negatively associated with R&D, supply chain agreements and patents. CVC-directors are negatively associated with patents and first product introductions. Adopting an abductive approach, we suggest potential mechanisms based on interviews with venture directors and CEOs and suggest future directions for venture boards scholarship. Scandals at private firms such as Theranos and Uber (when it was private) have highlighted both the influence that boards of directors have on these firms and the relative opacity with which they operate. While there is a considerable literature, both theoretical and empirical, on the boards of public companies, there is a relative paucity of research on governance in private firms. At the same time, the distinctive features of private firm governance may limit the applicability of insights from public boards; one difference is that in venture boards, directors often have significant ownership stakes in the companies as founders and representatives of venture capital firms (VCs) or the investment arms of other corporations (CVCs). As part of this special issue on the boards of private firms, we undertake an empirical investigation of the impact that these types of directors have on a variety of firm outcomes. We build on research on venture investing which hints at, but does not disentangle, the distinct impact of investors that have board seats versus investors that do not. Our analyses explores the impact that three types of venture directors- Founder-directors, VC-directors and CVC directors- have on strategic firm outcomes they are likely to influence in our context: inter-organizational ties, innovation and exit events. We conduct our study within a sector of the US medical device industry, where both venture-directors and venture-investors are prevalent and where previous research indicates they are likely to impact ventures. We take an abductive approach to analyze hand-collected longitudinal data on the directors of ventures and on the firms in this industry between 1997 and 2018. Overall, the results suggest that different types of directors can be significantly associated with ventures strategic outcomes, with each type of director bringing their unique focus and expertise to the table. For example, the results indicate that founder-directors may focus more on technology development and less on commercial development. For CVC-directors we do not find a significant association with interorganizational tie formation or exits, but are significantly negatively associated with innovation outcomes. Finally, while VC-directors are negatively associated with some kinds of interorganizational ties and patenting, they are significantly positively associated with faster exits via acquisitions and IPOs. We contribute to the emerging literature on venture boards through an abductive inquiry into how different types of venture directors are associated with some of the most important strategic outcomes involved in the growth, development and exits of ventures. These results control for investor and investment characteristics. The empirical relationships we document suggest a multitude of theoretical explanations that future researchers can build on to test hypotheses. Some of our surprising findings may have implications for key governance theories and their relevance to venture boards. For example, our results suggest that the agency perspective may be applicable to ventures through the principal-principal model but due to conflicts among different VC-directors, not among VC-directors and CVC-directors. By contrast, the resource dependence perspective can be extended by considering the relevance of organizational roles of resource providers as directors versus investors (e.g., CVC directors are neither particularly effective at providing complementary resources nor notably "shark-like" in misappropriating ventures) and that ventures may face significant coordination costs in orchestrating resources from different directors. Overall, our study suggests a more nuanced picture of conflict and cooperation in venture boards than has previously been identified and offers an opportunity for scholars to explore a broad array of theoretical explanations, including power and conflict.